Community Empowerment Efforts In Sustainable Ecotourism Management In North Sulawesi, Indonesia - Regina Rosita Butarbutar; Soemarno Soemarno (Indonesian Journal of Environment and Sustainable Development, 2012)
Tourism is one of the main economic sector of the North Sulawesi province. One of the highly developed tourism activities are ecotourism. Type of these tourist activities suggest the concept that was more concerned about the value of nature conservation and its environmental services in the destination sites to serve as tourist attractions. The number of foreign tourists visiting in North Sulawesi in 2006 reached 15.902 people and in 2007 reached 20,000 people while in 2008 reached 19.576 people. The number of foreign tourists every year increase  6.46% in 2007, and 13% in 2008. Globally the growth of ecotourism in 2004 reached three times faster than other tourism industries. Ecotourism is an integrated activity, prioritizes a balance between enjoying the nature beauties and maintain the sustainability of ecosystem services by involving participation of local people and tourists. This paper analyzes the environmental conservation efforts of nature and culture with an emphasis on empowering local communities, community participation in the ecotourism development, and an increase of local community welfare. Keywords: Natural resources, community empowerment, sustainable ecotourism.